Normalization of equation with linear distributed delay - I. S. Kashchenko (Моделирование и анализ информационных систем, 2009)
Some properties of the dynamics of a differential equation with the linear distributed delay is studied. In critical cases, which all have an infinite dimension, special equations - normal forms - were built.